When the Law Is No Longer Sharp Upwards: A Critical Study of Elite Impunity in Corruption Crimes - Fadhilah, Nurul; Samsidar, Samsidar; Rumalean, Zonita Zirhani (PT. Anagata Sembagi Education, 2025)
The phenomenon of elite impunity in corruption cases in Indonesia shows that there is a sharp gap between ideal legal norms and the reality of law enforcement practices that are full of power intervention. Although legal instruments such as the Corruption Law and the 2023 Criminal Code have normatively regulated sanctions against corruption, their implementation often favors the interests of political and economic elites. The judicial process is often characterized by weak independence of legal institutions, judicial mafia practices, and multiple interpretations of legal articles that open up space for abuse of authority. This inequality not only violates the principle of equality before the law, but also results in the erosion of the legitimacy of legal institutions and a decline in public trust in the democratic system. This study uses a normative juridical approach with critical legal theory analysis to dismantle power relations in the Indonesian legal system. The results emphasized the need for structural reform through strengthening the independence of law enforcement agencies, progressive regulatory revisions, and the formation of a critical legal culture with integrity. Without comprehensive reform, the law will only be a tool for the perpetuation of power, not an instrument of justice. This study recommends a transformation of the legal paradigm in order to ensure substantive justice and prevent the systemic practice of impunity of the elite.